PENGARUH EPS, DPS, DAN NPM TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR ENERGI YANG TERDAFTAR DI BEI PERIODE 2019-2023 DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL MODERATING - Mansur, Mohammad Sahel; Pramitasari, Triska Dewi; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
This study aims to analyze the influence of Earnings Per Share (EPS), Dividend Per Share (DPS), and Net Profit Margin (NPM) on stock prices in energy sub-sector companies listed on the IDX during the 2019-2023 period, with firm value as a moderating variable. The research sample includes 7 energy sub-sector companies listed on the Indonesia Stock Exchange over a five-year period, selected using purposive sampling technique. Data analysis and hypothesis testing are conducted using Structural Equation Modeling - Partial Least Square (PLS-SEM). The results of hypothesis testing using the Smart PLS 3.0.8 application show that Earnings Per Share (EPS) has a positive and significant effect on stock prices, Dividend Per Share (DPS) has a negative but not significant effect on stock prices, and Net Profit Margin (NPM) has a positive but not significant effect on stock prices. Additionally, firm value positively and significantly moderates the influence of Earnings Per Share (EPS) on stock prices.